2013
DOI: 10.1016/j.canlet.2013.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of in vitro cell motility and invasiveness of human malignant pleural mesothelioma cells through the HIF-1α-MUC1 pathway

Abstract: In this study, we examined the effects of hypoxia on the malignancy of human malignant pleural mesothelioma (MPM) cell lines, and found 1) hypoxia enhanced motility and invasiveness of human malignant pleural mesothelioma (MPM) cells; 2) this phenomenon resulted from increased expression of sialylated MUC1 through the activation of HIF-1 pathway; 3) two HIF-binding sites located in the promoter region of MUC1 were important for MUC1 transactivation under hypoxia. These findings are useful for better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Similar to the previous study [ 40 ], hypoxia enhanced the migratory and invasive properties in HMM cells. Additionally, the present study showed that hypoxia promoted EMT process in HMM cells.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the previous study [ 40 ], hypoxia enhanced the migratory and invasive properties in HMM cells. Additionally, the present study showed that hypoxia promoted EMT process in HMM cells.…”
Section: Discussionsupporting
confidence: 89%
“…Other evidences showed how miR-151-5p overexpression is linked with energy metabolism derangement and suggested a link with hypoxia 51 . This could explain their association with the overall survival that we observed here, since their high expression could promote the hypoxic microenvironment very well known to activate many signalling pathways involved in tumour initiation, progression and maintenance of MPM 52, 53 .…”
Section: Discussionmentioning
confidence: 53%
“…After knocking down MUC1 expression, reductions in HIF-1α protein expression, glucose uptake, and lactate release were observed [71]. Another study demonstrated that MUC1 facilitated HIF-1α translocation into the nucleus to act as a transcription factor for genes responsible for PDAC proliferation and invasion [72]. Moreover, the colocalization of the HIF-1α protein and VEGF mRNA identified via immunohistochemical analysis suggested that HIF-1α mediates the transcription of VEGF to induce angiogenesis in PDAC [73].…”
Section: Glycolysis and The Microenvironment Hypoxic Microenvironmentmentioning
confidence: 99%